Developing palm oil inventory control system using Ms Excel macro - Al-Hadi, Abdulsalam Khaled Abdullah; Siti Zubaidah, Ismail (Penerbit UMP, 2021)
The palm oil sector is just one of the popular sectors in Malaysia that offer one of the highest exports to Malaysia's economy. This study handles the research study of inventory control for Malaysian palm oil plantation. The existing inventory control cannot be running smoothly when the inventory are managed in different user interface systems which is by utilizing manual inventory control like Microsoft Excel and handwriting documents. Data collection was gathered with the targeted respondents, they are core members of the management team who have a great experience as well as understanding of their inventory system. In order to make PSS inventory control much easier as well as organized, an inventory application system is developed utilizing MS Excel Macro. The outcomes of this research study are a computerized supply control system that beneficial, crucial, and also much better substitute for a hand-operated administration system and quick handling.